Meningkatkan Keaktifan Belajar Siswa Melalui Model PBL Berbantuan Video Pada Materi Aku Pribadi Yang Unik Fase E di SMA Katolik Santo Fransiskus Assisi Samarinda - Fredi Manik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education is basically the main and first responsibility of parents. However, the state also has an obligation to facilitate faith education to be carried out well. One form of state support is by providing formal Catholic religious education and character education. And in the development of the world of education, curriculum changes have occurred in response to developments currently being used in the Merdeka curriculum. In the Merdeka curriculum, the values ​​of Pancasila will be emphasized. The school has implemented the Merdeka curriculum and in its implementation researchers observed and found several learning problems which also affected student learning outcomes. The main problem that must be resolved immediately is the problem of inactive student learning activity. This was also experienced by other educators, also based on several interviews and research journals. The low level of student learning activity can be overcome through a scientific approach. One of the studies Scientific research that is suitable to be applied to problems in the classroom is classroom action research. Expected through classroom action research, the problem of low student activity can be overcome and student learning achievement can increase. Classroom action research which is conducted using the Problem base learning model. This model considered suitable for overcoming student learning problems because can meet the criteria achievement Lesson objectives. The aim of this research is to determine the extent to which students are active in learning by applying the problem based learning method in increasing student activity in learning Catholic Religion for class X at SMAK Santo Fransiskus Assisi Samarinda odd semester of the 2023/2024 academic year. This research is classroom action research which consists of two cycles, the first cycle on 26 October 2023, the second cycle carried out on 06 November. The methods used in this classroom action research are problem based learning, data collection through observation, and written tests. Active learning about Catholic religious education with the material I Am a Unique Personality. There was an increase in student learning activity from cycle I, cycle II. The data on increasing student learning activities is that in cycle I the average percentage of activity scores for all students reached 72.3%, cycle II increased to 82.6%. By increasing the results of student learning activity per individual and per indicator, it has an effect on increasing student learning outcomes, namely cycle 50%, cycle II saw an increase in students who completed their studies by 80%. The results of the research show that the problem based learning method can increase student learning activeness in Catholic religious education with the Unique Personal Me material for class 10.5 students at SMAK St. Fransiskus Assisi Samarinda odd semester 2023/2024 academic year.